ANALISIS VARIASI KOMPOSISI PLA DENGAN TAMBAHAN PATI KULIT SINGKONG TERHADAP SIFAT UJI TARIK - rachman, aris; Dewi; Andita (Universitas Negeri Surabaya, 2026)
Plastic waste derived from petroleum-based materials poses serious environmental challenges, driving the development of environmentally friendly alternatives such as bioplastics. One promising approach is the incorporation of natural fillers into polylactic acid (PLA) to enhance its properties and biodegradability. This study aims to investigate the effect of varying compositions of PLA and cassava peel starch on the mechanical properties of bioplastics, particularly tensile strength, elastic modulus, and elongation. Bioplastics were fabricated using an injection molding process with cassava peel starch contents of 0 wt%, 10 wt%, 20 wt%, and 30 wt%. Tensile testing was conducted according to ASTM D638 standards using a Universal Testing Machine. The results indicate that the addition of cassava peel starch significantly influences the mechanical performance of the bioplastics. The optimal composition was achieved at 30 wt% starch content, exhibiting the highest tensile strength of 68.5 MPa, elastic modulus of 4515.15 MPa, and elongation of 6.3%. These improvements suggest enhanced interfacial bonding and more effective filler dispersion within the PLA matrix. The findings demonstrate that PLA–cassava peel starch bioplastics have strong potential as sustainable materials with improved mechanical performance for broader industrial applications.